Method Validation for the Determination of Carbamazepine in Spiked-saliva Using HPLC-UV for Therapeutic Drug Monitoring Application - Wibowo, Ari; Ningrum, Vitarani D.A.; Ilhamy, Rahma N. (Current Psychopharmacology, 2020)
Background: Carbamazepine has been used in the treatment of bipolar disorder, both in acute mania and maintenance therapy, particularly in developing countries. Not only its interaction with various drugs and auto-inducer nature, but the narrow therapeutic range of carbamazepine also makes monitoring necessary to guarantee the adequacy of its safety and therapeutic concentration. To date, the most common biological specimen used for therapeutic drug monitoring (TDM) purposes is still plasma, but saliva can become an alternative biological matrix since its level in saliva strongly correlates with carbamazepine plasma concentration. Objective: This study validated the bioanalytical method parameters used for carbamazepine in spiked-saliva in accordance with the Food and Drug Administration (FDA) criteria in the Guidance for Industry Bioanalytical Method Validation. Methods: HPLC-UV detector was employed at 285 nm λ with methanol: water: glacial acetic acid (65:34:1) as the mobile phase and C8 as the stationary phase (4.6x150 mm; 5 μm). Results: The linearity test in a range of 0.0 - 5 μg/mL carbamazepine concentration resulted in a correlation coefficient of 0.999 with 0.20 μg/mL LoD, 0.30 μg/mL LLoQ, and 0.61 μg/mL LoQ. The coefficient of variation and %diff in the selectivity, accuracy, and precision parameters remained below 20%, indicating fulfillment of the criteria for a bioanalytical method, while the average % recovery was more than 90%. Conclusion: The currently-developed bioanalytical method has fulfilled the stipulated validation criteria to be used for determining carbamazepine concentration in spiked-saliva as an alternative method for relative bioequivalence studies or TDM application in a clinical setting.
Keywords: ultraviolet detector